2003
DOI: 10.1212/01.wnl.0000069608.84542.46
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the striatal dopaminergic system in human narcolepsy

Abstract: Striatal D2/D3 dopaminergic receptors have been proposed to play a role in cataplexy. The authors studied the striatal presynaptic dopamine transporter and postsynaptic D2-receptors in seven patients with narcolepsy and seven control subjects using [123I](N)-(3-iodopropene-2-yl)-2beta-carbomethoxy-3beta-(4-chlorophenyl)tropane and [123I](S)-2-hydroxy-3-iodo-6-methoxy-([1-ethyl-2-pyrrolidinyl]methyl)benzamide SPECT. D2-receptor binding was elevated in narcolepsy (p = 0.017) and correlated with the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…The volume reduction of gray matter in narcoleptic patients could indicate a disease-related atrophy pattern, although they suggested that these findings require replication in an independent drugnaïve sample of patients. Eisensehr et al [49] assessed the striatal presynaptic dopamine transporter and postsynaptic D2-receptors in seven patients with narcolepsy and seven control subjects using [ 123 I](N)-(3-iodopropene-2-yl)-2beta-carbomethoxy-3beta-(4-chlorophenyl)tropane and [ 123 I](S)-2-hydroxy-3-iodo-6-methoxy-([1-ethyl-2-pyr rolidinyl]methyl)benzamide SPECT. D2-receptor binding was elevated in narcolepsy (P = 0.017) and correlated with the frequency of cataplectic and sleep attacks (r ≥ 0.844; P ≤ 0.017).…”
Section: Narcolepsymentioning
confidence: 99%
“…The volume reduction of gray matter in narcoleptic patients could indicate a disease-related atrophy pattern, although they suggested that these findings require replication in an independent drugnaïve sample of patients. Eisensehr et al [49] assessed the striatal presynaptic dopamine transporter and postsynaptic D2-receptors in seven patients with narcolepsy and seven control subjects using [ 123 I](N)-(3-iodopropene-2-yl)-2beta-carbomethoxy-3beta-(4-chlorophenyl)tropane and [ 123 I](S)-2-hydroxy-3-iodo-6-methoxy-([1-ethyl-2-pyr rolidinyl]methyl)benzamide SPECT. D2-receptor binding was elevated in narcolepsy (P = 0.017) and correlated with the frequency of cataplectic and sleep attacks (r ≥ 0.844; P ≤ 0.017).…”
Section: Narcolepsymentioning
confidence: 99%
“…In the present study, it was not possible to study nocturnal leg movements in more detail. There is evidence that dopamine has a crucial role in PLMS and RLS [41], and changes in the dopamine metabolism in narcolepsy have been observed [42]. It is not known whether these alterations develop simultaneously with the hypocretin deficiency or whether there are some compensatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using the canine model of narcolepsy suggest that hypoactivity of dopaminergic and noradrenergic circuits are among the major pathophysiological mechanisms in narcolepsy (38). Recent in vivo brain imaging studies in humans support this notion (9), and the disease is currently treated symptomatically with drugs that enhance monoaminergic (i.e., dopamine, norepinephrine) neurotransmissions (38). In vitro and in vivo studies clearly show that hypocretin peptides stimulate dopaminergic neurons in various brain sites (16,36), which also suggests that hypocretin deficiency may silence dopaminergic circuits.…”
Section: Discussionmentioning
confidence: 99%